2018
DOI: 10.3389/fimmu.2018.02253
|View full text |Cite
|
Sign up to set email alerts
|

Salivarian Trypanosomosis: A Review of Parasites Involved, Their Global Distribution and Their Interaction With the Innate and Adaptive Mammalian Host Immune System

Abstract: Salivarian trypanosomes are single cell extracellular parasites that cause infections in a wide range of hosts. Most pathogenic infections worldwide are caused by one of four major species of trypanosomes including (i) Trypanosoma brucei and the human infective subspecies T. b. gambiense and T. b. rhodesiense, (ii) Trypanosoma evansi and T. equiperdum, (iii) Trypanosoma congolense and (iv) Trypanosoma vivax. Infections with these parasites are marked by excessive immune dysfunction and immunopathology, both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
96
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 209 publications
(237 reference statements)
5
96
0
4
Order By: Relevance
“…This is attributed to the fact that these latter parasites acquired the ability to resist trypanolytic molecular complexes, expressed by humans and higher primates as part of the innate immune system [20][21][22][23][24]. Due to this reason, and its implications for human medicine, the T. brucei clade has received greater attention and is better characterized, despite being it having a lower, though still potent, worldwide impact on veterinary economy, than for example T. congolense (Subgenus Nannomonas) or T vivax (Sub-genus Dutonella) [25]. By parasitizing the haemo-lymphatic environment, trypanosomes must reconcile two seemingly conflicting requirements, namely, to avoid the immune responses of the mammalian host by rapid variation of their plasma membrane as well as efficiently acquire potentially scarce nutritive resources from their environment via the same plasma membrane [29].…”
mentioning
confidence: 99%
“…This is attributed to the fact that these latter parasites acquired the ability to resist trypanolytic molecular complexes, expressed by humans and higher primates as part of the innate immune system [20][21][22][23][24]. Due to this reason, and its implications for human medicine, the T. brucei clade has received greater attention and is better characterized, despite being it having a lower, though still potent, worldwide impact on veterinary economy, than for example T. congolense (Subgenus Nannomonas) or T vivax (Sub-genus Dutonella) [25]. By parasitizing the haemo-lymphatic environment, trypanosomes must reconcile two seemingly conflicting requirements, namely, to avoid the immune responses of the mammalian host by rapid variation of their plasma membrane as well as efficiently acquire potentially scarce nutritive resources from their environment via the same plasma membrane [29].…”
mentioning
confidence: 99%
“…It is however important to realize that B cell counts in the blood do not reveal whether B cell activation, the formation of plasma cells and antibody secretion, the induction of germinal center reactions, or the activation of CD4 + T follicular helper cell numbers and function, which are known to restrict T. congolense parasitemia [11,44], are impaired. However, this is highly likely since trypanosomes cause a general B cell depletion pathology, which is initiated by the very rapid disappearance of immature B cells in the bone marrow, as well as transitional and IgM + marginal zone B cells from the spleen, followed by a gradual depletion of Follicular B cells (FoB) [45,46]. Though the cause of B cell depletion is currently unknown, it was shown that the kinetics of this B cell loss and parasite outgrowth depends on different factors such as parasite virulence and the level of inflammation [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is highly likely since trypanosomes cause a general B cell depletion pathology, which is initiated by the very rapid disappearance of immature B cells in the bone marrow, as well as transitional and IgM + marginal zone B cells from the spleen, followed by a gradual depletion of Follicular B cells (FoB) [45,46]. Though the cause of B cell depletion is currently unknown, it was shown that the kinetics of this B cell loss and parasite outgrowth depends on different factors such as parasite virulence and the level of inflammation [45,46]. Therefore, the observed reduced B cell numbers in TgAlbCre-IL10 -/mice at the later phase of infection is most likely due to a higher/persistent inflammatory immune response [45,47].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years this parasite has occasionally caused havoc in Southern Europe due to illegal or ill-controlled import of infected livestock. The geographic distribution of all HAT and AT causing parasites and general aspects of the immunopathology related to their infections were recently reviewed by Radwanska et al (1).…”
Section: Introductionmentioning
confidence: 99%